Violence against Health Care Professionals and Facilities—Local Insights about a Global Malady - Nagpal, Neeraj; Nagpal, Nimisha; Kataria, Nilanshu; Parikh, Purvish (South Asian Journal of Cancer, 2020)
Acts of violence against health care professionals (especially doctors) as well as facilities are a growing global problem. In our country, it has taken an unfortunate dramatic turn of the involvement of a mob—a ragtag group of persons who organize and perpetrate the crime based on community, caste, religion, or political affiliations. This crucial factor is the fundamental difference in what we face as compared with the so-called Yi Nao phenomenon of China. In India, the mob gathers and indulges in acts of violence, intimidation, and blackmail at the behest of its “leader,” often having no direct relationship with the deceased patient. It is premeditated and systematic vandalism. Often it is also associated with financial gain to the perpetrators through extortion and blackmail, adding to the woes of the health care professionals and hospital facility. We discuss what is the primary goal and what is a byproduct in this cycles of violence against the people who are doing their best to save the lives of patients. Unless the governments and the courts take this matter seriously as well as follow-up with corrective measures, the future looks bleak for all stakeholders.
Keywords: doctors; medical negligence; soft targets; vulnerable; mob; inadequate; law